Impact Of Agribusiness Sub-Terminal (Sta) On Red Chili Agribusiness Performance In Deli Serdang Regency - Desi Novita (JASc (Journal of Agribusiness Sciences), 2020)
Red chilies are one of the strategic commodities in people's lives. The problem that is always faced in red chili farming is the long chain of marketing and marketing actors. This condition causes the bargaining position of farmers to become weak when dealing with agents. The purpose of this study was to determine how the impact of Red Chili Agribusiness Sub-Terminal (STA) on the performance of Red Chili agribusiness in Deli Serdang Regency. The data used by this research are primary and secondary data. Primary data obtained from red chili farmers who are permanent members of the STA. Data were analyzed through descriptive analysis and income analysis. The results showed that the presence of STA in Deli Serdang Regency had a positive impact both from the social and economic side in improving the performance of red chili agribusiness. The positive impacts include an increase in farmers' income by 22.82% from before the existence of STA, the emergence of new income sources, the level of closeness of social relations is getting better, price certainty and certainty of sales and shortening the marketing channels that occur.